2021
DOI: 10.1149/1945-7111/ac39da
|View full text |Cite
|
Sign up to set email alerts
|

Review—Single-Molecule Sensors Based on Protein Nanopores

Abstract: The recent development of single-molecule sensors (SMS), which detect individual targets one at a time, allows determination of ultra-low concentrations of structurally similar compounds from a complex matrix. Protein nanopores are one of the earliest methods able to resolve the signal from a single molecule, and have already been successfully employed in commercial DNA sequencers. The protein nanopore based SMS, however, remains challenging, largely because the quantitative single-molecule analysis requires r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 201 publications
(341 reference statements)
0
3
0
Order By: Relevance
“…Therefore, their detection is achieved through a specific blockade fingerprint, correlated with ensuing alterations in the net ionic current across it. The subsequent on- or off-line statistical analysis of the resulting current fluctuations, generates information regarding the analyte’s identity and its physical and chemical properties [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their detection is achieved through a specific blockade fingerprint, correlated with ensuing alterations in the net ionic current across it. The subsequent on- or off-line statistical analysis of the resulting current fluctuations, generates information regarding the analyte’s identity and its physical and chemical properties [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a voltage is applied across the nanopore, a major part of the electrical field is confined within a small radius around the nanopore (typically within a few microns), usually referred to as the capture radius [423,424]. Therefore, nanopores mostly capture the analytes available within the very tiny capture volume, which in turn limits the nanopore's performance [14,[425][426][427]. To overcome this limitation, Rahman et al have demonstrated an elegant solution developed on the previously described ARROW optofluidic platform that can improve the performance of nanopore sensing by increasing the detection rate of analytes [422].…”
Section: Electrical Methods For Single-molecule Experimentsmentioning
confidence: 99%
“…Biological nanopores can be produced from a series of materials, including pore-forming proteins, peptides, and DNA by insertion into lipid membranes, liposomes, or polymer membranes. 30,42,43 Apart from the aHL nanopore, other protein nanopores including aerolysin, 44,45 mycobacterium smegmatis porin A (MspA), [46][47][48] cytotoxic cytolysin A (ClyA) [49][50][51] and outer membrane proteins F (OmpF) 52,53 and G (OmpG), 54 have also been discovered (Fig. 3).…”
Section: Categories Of Nanoporesmentioning
confidence: 99%